Blended Learning: What kind of fit for the NetGen? - McDonald, S.; Howell, Jennifer (Australian Association for Research in Education (AARE), 2012)
This paper reports on a pilot project conducted with under-graduate students in pre-service teacher education programs. The aim of the project was to accommodate student requests for unit flexibility underpinned by a blended learning approach. The grounds for using this approach were: effective modelling of Information, Communication and Learning Technologies (ICLTs) pedagogies to pre-service teachers, flexibility for students in regards to the time required to attend lectures and review lecture materials, economic rationalism, and decreasing lecture attendance. The tools used to support the blended learning included video recordings of the PowerPoint presentations of the lectures using Camtasia Studio, online quizzes to support the key messages of the lectures, online discussion threads, and face-to-face two hour tutorials. Data were collected at the completion of three different curriculum units, and included student feedback (using Survey Monkey), and semi-structured focus group interviews. The findings will provide information on the preferred learning style of the NetGen cohort currently engaged in higher education. Furthermore the findings of this project will form the basis for a cross-institutional study, and reconceptualisation of service delivery for tertiary education students. This project will lead to a second study in which the parameters of the blended learning will be expanded and informed by the initial data.